2019
DOI: 10.1111/mcn.12907
|View full text |Cite
|
Sign up to set email alerts
|

The ABA intervention for improving breastfeeding initiation and continuation: Feasibility study results

Abstract: The UK has low breastfeeding rates, with socioeconomic disparities. The Assetsbased feeding help Before and After birth (ABA) intervention was designed to be inclusive and improve infant feeding behaviours. ABA is underpinned by the behaviour change wheel and offers an assets-based approach focusing on positive capabilities of individuals and communities, including use of a Genogram. This study aimed to investigate feasibility of intervention delivery within a randomised controlled trial (RCT). Nulliparous wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…It is imperative for organisations implementing a proactive peer support intervention for breastfeeding to understand the consumer experience to ensure programmes are acceptable, accessible, responsive and provide improved outcomes. 11 The current literature describing mothers' experiences of proactive breastfeeding support programmes is mainly limited to a few relatively small studies in Sweden 12 (proactive, telephone-based professional support), the UK [13][14][15][16] (predominantly face to face peer support models) and Australia 17 18 (mixture of peer/professional support face to face). Dennis' 19 20 Canadian study of the effect of proactive telephone-based peer support on breastfeeding, on which the RUBY study was based, reports maternal experiences including high rates of overall satisfaction and satisfaction with 'enough peer contact to help them with breast feeding'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…It is imperative for organisations implementing a proactive peer support intervention for breastfeeding to understand the consumer experience to ensure programmes are acceptable, accessible, responsive and provide improved outcomes. 11 The current literature describing mothers' experiences of proactive breastfeeding support programmes is mainly limited to a few relatively small studies in Sweden 12 (proactive, telephone-based professional support), the UK [13][14][15][16] (predominantly face to face peer support models) and Australia 17 18 (mixture of peer/professional support face to face). Dennis' 19 20 Canadian study of the effect of proactive telephone-based peer support on breastfeeding, on which the RUBY study was based, reports maternal experiences including high rates of overall satisfaction and satisfaction with 'enough peer contact to help them with breast feeding'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…While full details of intervention delivery and recruitment into the feasibility trial are reported elsewhere [21,22] a summary is provided as follows. The ABA intervention was an Infant Feeding Helper (IFH) peer support service delivered from~32 weeks gestation to5 months postnatal.…”
Section: Intervention Designmentioning
confidence: 99%
“…In the "Assets-based infant feeding help Before and After birth (ABA)" feasibility trial [21][22][23] a modified version of Darwent's infant feeding genogram [20] was used to increase women's assets for infant feeding. This paper explores infant feeding helpers and women's use and experience of the genogram as an intervention component in the ABA feasibility trial.…”
Section: Introductionmentioning
confidence: 99%
“…While full details of intervention delivery and recruitment into the feasibility trial are reported elsewhere (21,22) -a summary is provided as follows. The ABA intervention was an Infant Feeding Helper (IFH) peer support service delivered from ~32 weeks gestation to ~5 months postnatal.…”
Section: Intervention Designmentioning
confidence: 99%
“…In the Assets-based infant feeding help Before and After birth (ABA) feasibility trial (21,22) a modified version of Darwent's infant feeding genogram (20) was used to increase women's assets for infant feeding. This paper explores infant feeding helpers and women's use and experience of the genogram as an intervention component in the ABA feasibility trial.…”
Section: Introductionmentioning
confidence: 99%